PENGARUH STUDENT TEAMS ACHIEVEMENT DIVISION BERBANTUAN DOMINO-CHEM TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA - Rachmawati, Fitriyani Ikka; Sahputra, Rachmat; Rasmawan, Rahmat (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractPurpose of this research was to determine either able or no the differences in motivation and learning outcomes between students taught by STAD assisted learning model domino chem and conventional in class X in SMA PGRI 1 Pontianak on ion bonding and to determine how much influence the use of STAD learning model assisted by Domino chem to students learning outcomes. This research was quasi experiment with